2017
DOI: 10.1590/0037-8682-0323-2016
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional treatment with meglumine antimoniate in three patients with New World cutaneous leishmaniasis and large periarticular lesions with comorbidities

Abstract: Although New World cutaneous leishmaniasis is not itself a life-threatening disease, its treatment with systemic antimonials can cause toxicity that can be dangerous to some patients. Intralesional meglumine antimoniate provides a viable, less toxic alternative. Herein, we describe an alternative treatment with subcutaneous intralesional injections of meglumine antimoniate into large periarticular lesions of three patients with cutaneous leishmaniasis and comorbidities. This treatment was safe, successful, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…One interesting result of our study was that 7 patients treated with IL-MA had lesions larger than 3 cm, and no differences in cure rates or AEs was found compared to the subgroup with lesions smaller than 3 cm. Other authors reported a good response and safety with this local treatment in patients with lesions larger than 3 cm ( Oliveira-Neto et al, 1997 ; Vasconcellos et al, 2012 ; Pimentel et al, 2017 ; Duque et al, 2019 ). This fact may indicate that the size restriction in the ACL guidelines ( Brasil, 2017 ; PAHO/WHO, 2019 ) may be revised in the future due to a lack of scientific evidence to support this restriction.…”
Section: Discussionmentioning
confidence: 85%
“…One interesting result of our study was that 7 patients treated with IL-MA had lesions larger than 3 cm, and no differences in cure rates or AEs was found compared to the subgroup with lesions smaller than 3 cm. Other authors reported a good response and safety with this local treatment in patients with lesions larger than 3 cm ( Oliveira-Neto et al, 1997 ; Vasconcellos et al, 2012 ; Pimentel et al, 2017 ; Duque et al, 2019 ). This fact may indicate that the size restriction in the ACL guidelines ( Brasil, 2017 ; PAHO/WHO, 2019 ) may be revised in the future due to a lack of scientific evidence to support this restriction.…”
Section: Discussionmentioning
confidence: 85%
“…It is known that the use of systemic meglumine antimoniate can be lead to serious adverse effects, so the application in the lesion site showed to be an efficacious and more secure alternative to treat CL. Some authors have demonstrated that the intralesional MA is as effective as the systemic MA and had few adverse effects [4345]. It is important to note that, unlike in the articles included in this study, Vasconcellos et al (2014) [46] reported that one patient presented eczema after the treatment with intralesional meglumine antimoniate.…”
Section: Discussionmentioning
confidence: 89%
“…We emphasize the efficiency of MA infiltrations in lesions with areas greater than 900mm 2 and in those situated in topography where greater expertise from the medical personnel is required (including head and periarticular areas). The mastery of the infiltration technique and a good knowledge of local anatomy turn it safe for the treatment of any corporal segment [ 6 , 13 ]. Even though there were no differences between the treatment groups and the topography (cephalic segment and periarticular regions) of the cutaneous lesion, as found in several studies [ 13 , 21 , 22 , 24 , 27 , 36 ], it is recommended to perform controlled prospective studies.…”
Section: Discussionmentioning
confidence: 99%
“…The mastery of the infiltration technique and a good knowledge of local anatomy turn it safe for the treatment of any corporal segment [ 6 , 13 ]. Even though there were no differences between the treatment groups and the topography (cephalic segment and periarticular regions) of the cutaneous lesion, as found in several studies [ 13 , 21 , 22 , 24 , 27 , 36 ], it is recommended to perform controlled prospective studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation